2003
DOI: 10.1128/aem.69.4.1920-1927.2003
|View full text |Cite
|
Sign up to set email alerts
|

Nondigestible Oligosaccharides Enhance Bacterial Colonization Resistance against Clostridium difficile In Vitro

Abstract: Clostridium difficile is the principal etiologic agent of pseudomembranous colitis and is a major cause of nosocomial antibiotic-associated diarrhea. A limited degree of success in controlling C. difficile infection has been achieved by using probiotics; however, prebiotics can also be used to change bacterial community structure and metabolism in the large gut, although the effects of these carbohydrates on suppression of clostridial pathogens have not been well characterized. The aims of this study were to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
3
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(110 citation statements)
references
References 49 publications
6
98
3
3
Order By: Relevance
“…Hopkins and others showed that FOS, GOS, and inulin inhibit intestinal colonization of Clostridium difficile in vitro. 43,44 Prebiotic oligosaccharides induce antimicrobial effects by selectively stimulating the growth of intestinal protective bacteria. Such intestinal organisms can then secrete antimicrobial compounds and compete with disease-inducing bacteria for intestinal epithelial receptors, reducing their ability to colonize and affect the host, as mentioned above.…”
Section: Prebiotics and The Intestinal Microfloramentioning
confidence: 99%
“…Hopkins and others showed that FOS, GOS, and inulin inhibit intestinal colonization of Clostridium difficile in vitro. 43,44 Prebiotic oligosaccharides induce antimicrobial effects by selectively stimulating the growth of intestinal protective bacteria. Such intestinal organisms can then secrete antimicrobial compounds and compete with disease-inducing bacteria for intestinal epithelial receptors, reducing their ability to colonize and affect the host, as mentioned above.…”
Section: Prebiotics and The Intestinal Microfloramentioning
confidence: 99%
“…Recent studies suggest that Bacteroides, and possibly specific species of Bacteroides, have a role in preventing infection with Clostridium difficile (122,123). As detailed above, the development of the immune response that limits entry and proliferation of potential pathogens is profoundly dependent upon B. fragilis.…”
Section: Limiting Colonization Of the Gi Tract By Pathogensmentioning
confidence: 99%
“…Estudos in vitro e in vivo têm demonstrado que o ecossistema bacteriano intestinal normal representa barreira extremamente efetiva, em oposição a microorganismos patogênicos e oportunistas, através do equilíbrio entre as espécies de bactérias residentes (16,28) . Assim, situações de desequilíbrio entre espécies podem representar potencial ameaça para o surgimento de diversas doenças, associadas ou não à diminuição da defesa imunológica do hospedeiro (3) .…”
Section: O Sistema Digestório -Anatomia E Microbiotaunclassified